Acoustics of persuasion: a systematic review of prosodic features on the communicative attitudes of confidence - Valle, Dianete Angela; Souza, Lívia Maria Santos de; Strauss, Yonara Santana de Caetano; Dornelas, Rodrigo; Silva, Eduardo Magalhães da; Celeste, Letícia Correa (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2023)
Purpose: To review the literature regarding prosodic acoustic features found in communicative attitudes related to confidence, certainty, and persuasion. Method: A systematic review was carried out in the databases VHL, Web of Science, Science Direct, SciELO, and SCOPUS with no temporal restriction. Data Extraction: The data from each article was extracted based on the STROBE Statement checklist. To analyze the prosodic variables, the data were subdivided according to Couper-Kuhlen’s (1986) theoretical assumptions, and the variables were grouped into “temporal organization of speech,” “intensity,” and “pitch”. Conclusion: The data suggested that there are relevant but not consensual variables to characterize a persuasive speech and some variables can be considered as positive, negative, or neutral in different language contexts. The variables that stand out as relevant and are characteristic of the persuasive or confidant speech were faster speech speed and higher intensity. The only negative variable that stood out regarding persuasion was the increase in pitch.